The effects of Core-polarization on inelastic form factors of 10B - Ali A. Alzubadi (Iraqi Journal of Physics, 2012)
Inelastic transverse and longitudinal form factors of same parity have been studied for B 10 nucleus in the frame work of the shell model for many particles, by using He 4 as an inert core and the remaining particles were distributed in 3 / 2 1 / 2 1p ,1p which form the model space. The calculations of the present work based on the harmonic oscillator potential with fixed size parameter (b). Here we use the first order correction for the perturbation theory and the interaction from Cohen-Kurath (CK). Adding the core-polarization effects to form factors calculations gave a good agreement with the experimental data. Calculations have been performed for the transverse excited states of: (1 ,0 )at ( E  0.178MeV )  ,. (2 ,0)at(E  3.587MeV),  (3 ,0)at(E  4.774MeV),  and longitudinal ( 2 ,1)at( E  5.164MeV )  .